2016
DOI: 10.3748/wjg.v22.i38.8568
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the uncertainty: Risk factors and clinical relevance of P1 lesions on small bowel capsule endoscopy of anemic patients

Abstract: AIMTo identify risk factors for P1 lesions on small bowel capsule endoscopy (SBCE) and to describe the natural history of anemic patients with such type of lesions.METHODSOne hundred patients were consecutively selected for a case-control analysis performed between 37 cases with P1 lesions and 63 controls with negative SBCE. Age, gender, comorbidities and regular medication were collected. Rebleeding, further investigational studies and death were also analyzed during the follow-up.RESULTSNo significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…The result of our study enrolled patients with OGIB with negative CT and CE, which is similar to the previously published results [ 28 ]. In the above-mentioned study, the causative lesions for IDA were diagnosed using conventional endoscopies [ 28 ]. Whereas in our study, additional SB evaluation was conducted in 81.8% (9/11) of the patients for diagnosis of recurrent SB bleeding.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The result of our study enrolled patients with OGIB with negative CT and CE, which is similar to the previously published results [ 28 ]. In the above-mentioned study, the causative lesions for IDA were diagnosed using conventional endoscopies [ 28 ]. Whereas in our study, additional SB evaluation was conducted in 81.8% (9/11) of the patients for diagnosis of recurrent SB bleeding.…”
Section: Discussionsupporting
confidence: 88%
“…Contrary to our expectations, in this study, there was no significant difference of rebleeding rate (18.4% vs. 17.4%) between the P0 and P1 groups. In a study performed between P0 ( n = 63) and P1 ( n = 37) lesions on CE in patients with IDA, subgroup analysis of 87 patients with a longer follow-up duration (>1 year) showed that rebleeding or IDA recurrence was not significantly different between the P0 and P1 lesions (21.6% vs. 37.0%, p = 0.349) [ 28 ]. The result of our study enrolled patients with OGIB with negative CT and CE, which is similar to the previously published results [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors consider that some SBCE-positive findings do not need a subsequent DAE, an invasive procedure, since some patients could be better managed with other treatment/diagnostic strategies, i.e., iron replacement therapy for some P1 or P2 lesions, or radiological methods for subepithelial lesions. The authors believe that the PM threshold concerning referral for DAE should be revised, as a significant proportion of patients can be managed by other treatment modalities (conservative, medical, surgical) as demonstrated by our series and Rondonotti’s study [6], as well as other published evidence [26, 27]. The referral rate from SBCE to DAE was similar between centers, and this was not affected by the DAE availability in CHVNG/E in relation to CHLO.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, recent data confirm that negative SBCE provides adequate evidence of a low risk of rebleeding. Such patients can therefore be safely managed with watchful waiting 50 53 85 86 . Nevertheless, SB neoplasia and diverticula are mural-based lesions that can cause IDA but can be missed at SBCE, and for which CTE has been shown to have higher sensitivity 9 17 87 .…”
Section: Iron-deficiency Anemiamentioning
confidence: 99%